THE SIGNIFICANCE OF BILINGUAL DICTIONARIES IN TEACHING ENGLISH AT SCHOOL, LYCEUM, COLLEGE AND HIGHER EDUCATIONAL ESTABLISHMENTS - Ruzimov, Sh. (SCIENCE and SOCIETY, 2018)
In the article compiling principles of English-Uzbek and Uzbek-English dictionaries were critically investigated and there were given practical recommendations for improving their role in teaching English at schools, lyceums, colleges and higher educational establishments.
Keywords: lexicography; encourage; synonym; stress; principles; critically; recommendations; to work out; the whole system; scientific